Analysis of Shoreline Changes in Nusaniwe District, Ambon City, Using Landsat 8-9 Satellite Imagery - Reza Mulyadi; Warniyati; Tri O. Sihombing; Monic R Tutkey (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The coastal area of Nusaniwe District in Ambon City is a dynamic and dense area of human activity, such as ports, settlements, and industries. This condition makes the area vulnerable to shoreline changes triggered by natural factors and human activities. This study aims to analyze changes in the coastline of Nusaniwe District during the period 2015-2024 using Landsat 8-9 satellite imagery which was analyzed using the Digital Shoreline Analysis System (DSAS) method based on Net Shoreline Movement (NSM) and End Point Rate (EPR) parameters. The results of the analysis show that the change in the coastline in this region is dominated by retreat, especially in area C (Negeri Latuhalat) with an average change of 11.98 meters from 2015-2024. Meanwhile, area E (Wainitu Village) experienced an advanced coastline with an average change of 4.28 meters. The total area of identified coastline changes is 35,573 Ha, consisting of 24,867 Ha of backward coastline and 10,707 Ha of advanced coastline. These significant changes are influenced by human activities and coastal environmental conditions. This research is expected to be the basis for spatial planning and disaster mitigation efforts in the coastal area of Ambon City. Keywords: Shoreline Change, Receding Coastline, Forward Coastline, Abrasion, Accretion, Landsat, DSAS, Nusaniwe District